THE DEVELOPMENT OF AN EVALUATION MODEL FOR THE CHARACTERISTICS OF THE STUDENT TEACHERS QUALITY: APPLYING THE UTILYZATION-FOCUSED EVALUATION - (Benjawan Intawong), เบญจวรรณ อินต๊ะวงศ์; (Pakorn Prachanban), ปกรณ์ ประจันบาน; (Sirichai Kanjanawasee), ศิริชัย กาญจนวาสี (Journal of Education and Innovation, 2018)
The purpose of this research was studying on factors and indicators the characteristics of the student teachers quality, constructing the evaluation model, trying out the evaluation model and summative evaluating of the evaluation model. The samples were the 615 student teachers in Faculty of Education from the multistage random sampling method. The skill measurement instruments of the student teachers quality were shown in three types: a Knowledge test, Spiritual Teacher Evaluation form and Skill and Ability Evaluation form. The content validity, difficulty index, discrimination index, reliability, constructs validity, normal distribution T - Score and cut-Scores were analyzed. The results of this research were as: the characteristics of the student teachers quality composed of 3 factors; Knowledge 13 indicators, Spiritual Teacher 3 indicators, and Skill and Ability 11 indicators.The evaluation model for the characteristics of the student teachers quality by applying the utilization-focused evaluation was consisted of 4 steps: input, process, output and feedback. The results of the trying out revealed that The number of students passing the Knowledge cut- Scores, Spiritual Teacher cut- Scores and Skill and Ability cut- Scores were 71.88%, 100% and 93.75. The results of summative evaluating of the evaluation model found that it was well qualified with propriety, utility, feasibility and accuracy.